Urban ecosystem Services in Latin America: mismatch between global concepts and regional realities? (2019)
Latin America and the Caribbean (LAC) is one of the most urbanized and biologically diverse regions in the world but is often characterized by weak environmental governance and socioeconomic inequalities. Given large expanses of intact biomes, a long history of pre-Colombian civilizations, and recent urbanization trends, the urban ecosystem services (UES) concept has the potential to address issues of well-being for its citizens. We review relevant regional and global literature and use expert-based knowledge to identify the state of the art of the UES concept as applicable to green spaces in LAC and elucidate three overarching guidelines for management and future research needs: 1. LAC cities can be socio-ecologically unique; 2. Drivers of UES in LAC can be different than in other regions; and 3. Context and demand need to be accounted for when valuing UES. Overall, we show that research on UES is mostly from the global north and rarely accounts for the diverse and complex socio-political and ecological drivers of LAC’s urbanization processes. We find that, as in other regions, the biophysical context and land use policies play a major role on UES provision. However, socioeconomic inequalities and weak governance are key drivers in UES supply and demand in LAC. Context-specific information on how to promote, educate, and apply UES is particularly important, not only in LAC, but in other regions where inequities, rapid urbanization, and climate change effects are stressing socio-political and ecological systems and their adaptive capacities. Standardized approaches from developed countries should be used to complement - not substitute – LAC context specific approaches for studying and applying UES. We suggest that improved research funding and local governance can also provide critical strategies, information and the means for more effective management, planning, and equitable provision of UES. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.